2012
DOI: 10.1155/2012/930710
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3: A Bifunctional Role in Cell Death Pathways

Abstract: Although glycogen synthase kinase-3 beta (GSK-3β) was originally named for its ability to phosphorylate glycogen synthase and regulate glucose metabolism, this multifunctional kinase is presently known to be a key regulator of a wide range of cellular functions. GSK-3β is involved in modulating a variety of functions including cell signaling, growth metabolism, and various transcription factors that determine the survival or death of the organism. Secondary to the role of GSK-3β in various diseases including A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(186 citation statements)
references
References 131 publications
8
173
1
4
Order By: Relevance
“…Moreover, GSK-3b activation can play a role in NF-kB activation in vivo and in vitro (24,25), implying that during ER stress, GSK-3b activation may be involved in activation of the NF-kB-mediated inflammatory pathway. A number of recent findings have linked GSK-3b to apoptosis (32,33). Our finding that GSK-3b activation is involved in the regulation of IL-1b and TNF-a transcription in response to ER stress is novel and important.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, GSK-3b activation can play a role in NF-kB activation in vivo and in vitro (24,25), implying that during ER stress, GSK-3b activation may be involved in activation of the NF-kB-mediated inflammatory pathway. A number of recent findings have linked GSK-3b to apoptosis (32,33). Our finding that GSK-3b activation is involved in the regulation of IL-1b and TNF-a transcription in response to ER stress is novel and important.…”
Section: Discussionmentioning
confidence: 66%
“…It is reported that GSK-3β regulates apoptotic pathways directly or indirectly. It directly triggers the mitochondrial apoptosis cascade by promoting Bax translocation to mitochondria [49] and indirectly leads to canonical Wnt pathway-mediated apoptosis through phosphorylation of β-catenin [50] . Here, we also investigated the regulatory effects of LX2343-mediated GSK-3β inhibition against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,30,31 GSK-3β was found to be inhibited by activation of AKT in L. donovani-infected condition as upon use of dominant negative AKT, phosphorylation-mediated inhibition of GSK-3β was not seen. As GSK-3β is known to inhibit or induce apoptosis depending on the stimulus, 32 we transfected cells with constitutively active GSK-3β constructs which in infection resulted in significant drop in parasite burden and anti-inflammatory responses while increasing the overall proinflammatory responses and mitochondrial membrane permeabilization, indicating that GSK-3β works as a pro-apoptotic protein in Leishmania infection. This increase, however, was not at par with that seen in AKT-inactivated infected cells indicating the possible role of multiple targets working downstream of AKT.…”
Section: Discussionmentioning
confidence: 99%